(untitled) (Research, Society and Development, 2023)
The objective was to evaluate the performance of a drip irrigation system, using autonomous photovoltaic energy. The experiment was composed of a photovoltaic module directly connected to the water pump, with the discharge conducted to an irrigation system formed by four drip pipes installed on a bench. The tests were carried out with the energy supply, using the fixed and solar tracking system, so that the two treatments are characterized as follows: T1 - Fixed and Level and T2 - Tracking and Level. The collectors were positioned for flow measurement at 9:00 AM, 10:00 AM, 11:00 AM, 12:00 PM, 1:00 PM, 2:00 PM, 3:00 PM, 4:00 PM, and 5:00 PM. In the energy system, voltage, current and irradiation parameters were measured; in irrigation, the water flow rate, and initial and final service pressure. The Distribution Uniformity Coefficients (DUC) and Christiansen Uniformity Coefficient (CUC) were calculated in addition to the Shewhart control chart and the process capability index. The results showed greater stability when using the tracking system, with CV of 65.28% and power of 64.71W, for the fixed system, and CV of 16.31% with 142.40W with the tracking system. Both treatments exceeded 90%, in uniformity, with the DUC reaching minimum necessary value of the process capacity index to maintain excellent levels. Therefore, the better energy generation of the tracking system positively influenced irrigation, which can be seen mainly in the Shewhart control charts.